Approximations to g-renewal functions - Rangan, Alagar; MoghimiHadji, Ehsan (Emerald Group Publishing Ltd, 2011)
Purpose - The purpose of the paper is to provide useful approximations for the computation of g-renewal function, since no closed form solution of such a function is available Design/methodology/approach - One of the methods uses a simple identity to obtain an approximation. The second method uses the Riemann sum to approximate the integrals to obtain a method of successive approximation. Findings - The two methods provide satisfactory approximations with the relative errors in the computations are well within the acceptable limits. The accuracy of the successive approximation method could be improved with finer partition of the interval integration but at the cost of computational time. Research limitations/implications - The computational time increases for the evaluation of the renewal function for increasing values of t. Originality/value - The paper provides easy to evaluate approximations for g-renewal functions, which do not have closed form analytical solutions.
Keywords: General repair; g-renewal function; Approximation; Numerical solution; Reliability management; Function approximation